AKIBAT HUKUM TERHADAP PENOLAKAN EKSEKUSI PUTUSAN ARBITRASE (STUDI KASUS DANNY SIHANOUK DE MITA VS SALVAGE B.V.) - Mikael Brian (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
Arbitration is an alternative dispute resolution outside the court. arbitration generally has the nature of a final award. Arbitration is carried out by the disputing parties based on an arbitration agreement, so there has been an agreement regarding the dispute settlement route they will face. Even so, we are also often presented by several individuals who reject the arbitration award, which in essence is final. Therefore, in this journal the author wants to examine juridically the implications of rejecting the execution of an arbitration award. The author also wants to examine the legal consequences of refusing to execute the arbitration award. Therefore, in this article, the author will elaborate the implementations of an arbitration award that deviates from the legal provisions and conduct a more in-depth study, author tries to elaborate the legal consequences between them.